Pertanggungjawaban Pidana Dalam Tindak Pidana Lingkungan Hidup Yang Dilakukan Oleh Korporasi Pasca Peraturan Mahkamah Agung Nomor 13 Tahun 2016 - Fitriani Rahmadia; Hari Sutra Disemadi; Nyoman Serikat Putra Jaya (Unram Law Review, 2020)
Corporations are organized groups of people and / or properties, both in the form of legal entities or non-legal entities. In relation to the corporation as a legal subject in environmental crime, it is formulated in Article 1 number 32 of the Law Number 31 Year 2009 about Environmental Protection and Management, each person is an individual or business entity, both legal entities and non-legal entities. The context of corporate crime in the environment is still not solid enough to ensure corporations in criminal sanctions because there is no legal basis regarding the procedures for handling environmental crimes committed by corporations. The Supreme Court Regulation Number 13 of 2016 concerning Procedures for Handling Corporate Crime provides a basis for enforcement of criminal law, then the purpose of writing this article is to find out the form of criminal liability for corporations for environmental crimes and legal consequences after the Supreme Court Regulation Number 13 of 2013.The type of research used is legal research which is included in the normative legal research typology where this study focuses on positive legal norms in the form of legislation. The theory used by the author in analyzing is using the theory of criminal liability which is based on the principle of legality. The conclusions include: criminal sanctions that can be applied to corporations based on Article 4 of Supreme Court Regulation Number 13 of 2016 are in the form of criminal fines, additional crimes, and disciplinary actions except prisons and confinement. Last, the legal consequences of the application Article 25 Supreme Court Regulation Number 13 of 2016 with the principal criminal is a criminal fine and then the criminal added according to the law governing environmental criminal acts is the Law Number 32 Year 2009 concerning Environmental Protection and Management.